Use of intraoperative ex VIVO fluorescence confocal microscopy to identify ganglionic bowel in Hirschsprung’s DISEASE: A case series - Donatella Di Fabrizio; Irene Tavolario; Francesca Mastroberti; Edoardo Bindi; Alessandra Filosa; Gaia Goteri; Giovanni Cobellis (Journal of Pediatric Surgery Case Reports, 2025)
Introduction: Hirschsprung's disease requires precise intraoperative identification of ganglionic bowel to ensure successful pull-through. Ex vivo fluorescence confocal microscopy (FCM) may offer a rapid, real-time diagnostic adjunct. Case Presentations: Case 1: A 2-month-old male presented with delayed meconium passage, abdominal distension, and bilious vomiting. Contrast enema revealed a rectosigmoid transition zone, and rectal suction biopsy confirmed aganglionosis. He underwent laparoscopic Soave-Georgeson pull-through. Intraoperatively, seromuscular biopsies were stained with acridine orange and fast green and examined using FCM. Digital images were analyzed remotely by a pathologist, who confirmed the presence of ganglion cells within 5 minutes. The pull-through was completed based on this assessment. Postoperative recovery was uneventful, and at 18-month follow-up, the child had normal bowel function and growth. Case 2: A 3-month-old female presented with chronic constipation, vomiting, and failure to thrive. Imaging and rectal biopsy confirmed Hirschsprung's disease. She underwent laparoscopic pull-through guided by FCM, following the same protocol as in Case 1. Real-time identification of ganglion cells allowed for prompt selection of the pull-through segment. The postoperative course was uncomplicated. At 12-month follow-up, the child had normal stooling patterns and appropriate weight gain. Conclusion: Intraoperative ex vivo fluorescence confocal microscopy seems to be a fast and reliable method for the identification of ganglionic bowel during the pull-through procedure for the management of Hirschsprung disease.